Oskar Schindler : the untold account of his life, wartime activities, and the true story behind the list - Crowe, David M. (Westview Press, 2004)
"Schindler is best known for saving over a thousand Jews by putting them on the famed "Schindler's List" and then transferring them to his factory in today's Czech Republic. In reality, Schindler played only a minor role in the creation of the list through no fault of his own. Plagued by local efforts to stop the movement of Jewish workers from his factory in Krakow to his new one in Brunnlitz, and his arrest by the SS who were investigating corruption charges against the infamous Amon Goth, Schindler had little say or control over his famous "List. The tale of how the "List" was really prepared is one of the most intriguing parts of the Schindler story that Crowe tells here for the first time." "Forced into exile after the war, success continually eluded Schindler and he died in very poor health in 1974. He remained a controversial figure, even in death, particularly after Emilie Schindler, his wife of forty-six years, began to criticize her husband after the appearance of Steven Spielberg's film in 1993."--BOOK JACKET.